Effects of Phaffia rhodozyma on microbial community dynamics and tobacco quality during tobacco fermentation - Mai, Jing; Zhu, Ming-Jun; Hu, Bin-Bin; Zhang, Hong; Liu, Zhong-Hua; Sun, Jian-Feng; Hu, Yang; Zhao, Lu (Frontiers in Microbiology, 2024)
Carotenoids are important precursors of various aroma components in tobacco and play an important role in the sensory quality of tobacco. Phaffia rhodozyma is a species of Xanthophyllomyces capable of synthesizing a highly valuable carotenoid-astaxanthin, but has not yet been used in improving tobacco quality. In this study, P. rhodozyma could grow and produce carotenoids in tobacco extract, with a maximum biomass of 6.50 g/L and a maximum carotenoid production of 36.13 mg/L at 100 g/L tobacco extract. The effects of P. rhodozyma on the dynamic changes of microbial communities and metabolites in tobacco were revealed based on microbiome and metabolomics techniques. Meanwhile, the correlation analysis combined with microbiome and metabolomics showed that P. rhodozyma was significantly positively correlated with 11 metabolites such as 6-hydroxyluteolin and quercetin. Furthermore, the contents of alcohols, ketones and esters, which were important aromatic components in fermented tobacco, reached 77.57 μg/g, 58.28 μg/g and 73.51 μg/g, increasing 37.39%, 265.39% and 266.27% compared to the control group, respectively. Therefore, the aroma and flavor, and taste scores of fermented tobacco increased by 0.5 and 1.0 points respectively, leading to improved sensory quality. This study provides a novel microbial fermentation method to improve tobacco quality.